Analysis of Factors that Influence Nurse Career Development in Dr. Soedjono Selong Hospital - Yuliyanti, Sasteri; Hadi, Muhammad; Arofiati, Fitri (Jurusan Keperawatan FIKES UNSOED, 2020)
Background: Nurses are the majority health workers in hospitals that have a very large contribution in improving the quality of health services provided to patients. Based on the research of Sulung (2013), it was found that career development was a variable that significantly affected the quality of nursing services. Objective: To determine the factors that influence nurse career development. Method: This study used a cross sectional approach with a sample of 103 nurses. Data was collected using a questionnaire compiled by researchers. Data analysis was performed in univariate, bivariate (chi-square) and multivariate (multiple logistic regressions). Results: Factors related to career development were: displacement/rotation (p = 0.003), opportunity to grow and develop (p=0.001), and organizational policy (p=0.032). The most dominant displacement/rotation factor is related to career development (OR =10,820). Conclusion: In developing nurse careers, hospitals must pay attention to aspects of displacement/rotation, opportunities to grow and develop and organizational policies.